Author Correction: Myoblasts and macrophages are required for therapeutic morpholino antisense oligonucleotide delivery to dystrophic muscle - James S. Novak; Marshall W. Hogarth; Jessica F. Boehler; Marie Nearing; Maria C. Vila; Raul Heredia; Alyson A. Fiorillo; Aiping Zhang; Yetrib Hathout; Eric P. Hoffman; Jyoti K. Jaiswal; Kanneboyina Nagaraju; et al. (Nature Communications, 2018)
The originally published version of this Article contained an error in Figure 6. In panel b, the top graph (BrdU 21–24d) and the bottom graph (BrdU 28–31d) were inadvertently swapped. This error has now been corrected in both the PDF and HTML versions of the Article.